Uma análise da aplicabilidade dos protocolos firmados no âmbito do Mercosul: a dispensa de homologação de sentença e a execução - Morais, Wilson Leite de (2006)
Upon the creation of Mercosul came the need to proceed with the process of cooperation in terms of contractual and jurisdictional matters by means of passing those new laws established in its original treaty, the so-called Treaty of Asuncion, and in its complementary protocols. The purpose of this present work is to analyze the applicability in Brazil of those main protocols entered within the scope of Mercosul, particularly in regard to the exemption of the homologation sentence and the execution, with a focus on the Treaty of Asuncion, the Buenos Ayres Las Leñas Protocols, the Writs of Prevention and the CIDIP-V (V Inter- American Specialized Conference on International Private Law) which, despite not being subscribed within Mercosul, is relevant because it concerns contractual matters to be applied in the Americas. From the analysis of these laws one can see that important facts are not being considered in Brazil, mainly as a result from the posture adopted by its Supreme Court of not exempting sentences from the Mercosul of homologation. Thus, there is no extraterritorial sense given to sentences from other Mercosul country-members. As it is a process of cooperation, and due to the fact that neither its principles nor its additional protocols are being considered, one may say that the juridical sources of this law of integration are being disregarded. As a conclusion, it is important that the Supreme Court of Brazil consider protocols entered in the scope of Mercosul as a process of cooperation and integration. In other words, the Supreme Court of Brazil should reconsider its posture and adequate itself to the principles of the Federal Constitution of 1988 whose disposition in article 4, sole paragraph, establishes that Brazil shall seek for the integration of Latin America